(3OdGFd GdNjQGJ hThGQb GdCfhGQ aj PcQ GdUdGI Ydi GdfHj GdeNJGQs - (3GdLRhdj, eMeO Hf SdjeGf Hf YHO GdQMef, J(B870(3g`s
(3ChdgG (B:s
(3hbGdCHh YHO Gddg eMeO Hf SdjeGf GdLRhdjGdMeO ddg GdPj gOGfG ddEjeGf hHYO gPG aGdZQV aj gPG GdcJGH PcQ GdUdGI Ydi GdfHj Udi Gddg Ydjg hSde hSejJg HcJGH OdGFd GdNjQGJs
(3BNQgG (B:s
(3Gddge Yde GdNGFajf hEfGHI GdeNHJjf hENdGU GdeDbJjf hTcQ GdUGHQjf hJhHI GdUGObjf cGed OdGFd GdNjQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 151s
(3eYLe GdeDdajf(B: 3 / 333s
(3cTa GdXfhf(B: 1 / 759s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs